PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN PERANGKAT DESA - MOCH. MAHRUSIL MAHBUB; MOH. NASIKH (STIE Indonesia Malang, 2023)
The purpose of this study was to analyze the effect of motivation and work discipline partially on service quality, analyze simultaneously the effect of motivation and work discipline simultaneously on service quality, and analyze the dominant influence between motivation and work discipline variables on service quality. Data analysis techniques in this study were grouped into two, namely: descriptive statistical analysis and inferential statistical analysis (multiple linear regression). The results of the study show that motivation and discipline partially have a significant effect on employee performance. Motivation and work discipline simultaneously have a significant effect on employee performance. Other results can be seen motivational variables that have a more dominant effect on employee performance.Keywords: motivation, work discipline, service quality